Connecting social disorganization to broken windows and routine activities. (4th May 2018) - Piscitelli, Anthony; Doherty, Sean
Abstract : Routine Activity Theory, Broken Windows Theory, and Social Disorganization Theory each attempt to explain the spatial distribution of neighbourhood crime. This paper explores how these theories relate to neighbourhood crime. A concept map integrating key concepts from the theories comprehensively describes the causes of neighbourhood crime. In particular, the map highlights the concept of Ecological (Dis)advantage as a key link between Routine Activity Theory and Social Disorganization Theory. Combining these theories explains more about the causes of neighbourhood crime than any one individual theory acting alone. Key Messages: Routine Activity Theory, Broken Windows Theory, Social Disorganization Theory, and Ecological (Dis)advantage each contribute uniquely to explaining neighbourhood crime. Integrating these theories can provide a more comprehensive framework to describe the causes of crime in neighbourhoods. The concept of Ecological (Dis)advantage is a particularly key link between Routine Activity Theory and Social Disorganization Theory.